The Effect of Housing and Feeding Systems on Growth and Survival Rate of Chickens up to Maturity Age - International Livestock Research Institute (International Food Policy Research Institute, 2018)
This data was generated as a part of the research project undertaken to evaluate the influence of feeding and housing systems on the growth rate, survival rate, and diseases and loss incidences of local chicken flocks in three villages of Babati, Tanzania. A total of 912 chicks of six weeks of age were used for this study. The chicks were randomly allocated to four feeding and housing systems namely housed with home-made balanced feed, housed with non-balanced feeds (locally available ingredients mainly maize bran and grains), non-housed (scavenging) with supplementation of home-made balanced feeds, and non-housed (scavenging) relying entirely on scavengeable feed resources with rare supplementation of non-balanced feeds (locally available ingredients mainly maize bran/ grains/ kitchen left over) The chickens were monitored to the twentieth week of age when they attained their maturity.